MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MODEL PEMBELAJARAN JIGSAW KELAS VIII D MTs NEGERI DARMA - LELA NURLAELA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
The research action taken was the application of the Jigsaw Learning model which was carried out in class VIII D of MTs Negeri Darma in the Odd Semester of the 2015/2016 Academic Year. This study aims to increase student activity and learning outcomes by applying the Jigsaw learning model. The minimum completeness criterion for Social Studies class VIII D at MTs Negeri Darma is 70. Classical absorption is obtained by at least 85% of the number of students in the class who have achieved an individual score of 70. By using the Jigsaw learning model students learn with feelings of pleasure, students respond well and more easily understand the material. There is an increase in student activity, students are not limited to receiving material but are actively seeking and conveying information in group discussions. Based on research, students who actively seek information in the Expert Team in cycle 1 22.22% in cycle 2 increase to 30.55%, students who actively seek information in the Origin Team in cycle 1 27.78% in cycle 2 to 36.11%, students who active asking When presenting in cycle 1 16.67% in cycle 2 rose to 27.78%, students who did activities alone in cycle 1 33.33% in cycle 2 decreased to 5.55%. The results of the research show that the acquisition of data on student learning outcomes is in the process of using the Jigsaw learning model. Students who scored less than 70 reached 11.11% (4 students) while students whose grades were completed reached 88.89% (32 students), in this case it appears that classical learning completeness has been completed. From these data it can be concluded that learning is carried out using the Jigsaw learning model (Team of Experts) which is significant for increasing student activity and learning outcomes. ABSTRAKTindakan Penelitian yang dilakukan adalah Penerapan model Pembelajaran Jigsaw yang dilaksanakan di kelas VIII D MTs Negeri Darma Pada Semester Ganjil Tahun Pelajaran 2015/2016. Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa dengan menerapkan model pembelajaran Jigsaw. Kriteria ketuntasan minimal untuk mata pelajaran Ilmu Pengetahuan Sosial kelas VIII D di MTs Negeri Darma adalah 70. Daya serap klasikal diperoleh nilai sekurang-kurangnya 85% dari jumlah siswa di kelas tersebut yang telah mencapai nilai perorangan sebesar 70. Dengan menggunakan model pembelajaran Jigsaw siswa belajar dengan perasaan senang, siswa merespon dengan baik dan lebih mudah memahami materi. Adanya peningkatan aktivitas siswa, siswa tidak sebatas menerima materi tetapi aktif mencari dan menyampaikan informasi dalam diskusi kelompok. Berdasarkan penelitian Siswa aktif mencari informasi dalam Tim Ahli dalam siklus 1 22,22% di siklus 2 naik menjadi 30,55%, Siswa yang aktif mencari informasi dalamTim Asal dalam siklus1 27,78% di siklus 2 menjadi 36,11%, siswa yang aktif bertanya Ketika presentasi di siklus 1 16,67% di siklus 2 naik menjadi 27,78%, siswa yang beraktifitas sendiri di siklus 1 33,33% di siklus 2 turun menjadi 5,55%. Hasil penelitian menunjukan perolehan data hasil belajar siswa dalam proses menggunakan menggunakan model pembelajaran Jigsaw. Siswa yang mendapat nilai kurang dari 70 mencapai 11,11 % (4 siswa) sedangkan siswa yang nilainya tuntas mencapai 88,89% (32 siswa), dalam hal ini nampak ketuntasan belajar secara klasikal sudah tuntas. Dari data tersebut diperoleh kesimpulan bahwa pembelajaran dilaksanakan dengan model pembelajaran Jigsaw (Tim Ahli) signifikan terhadap peningkatan aktivitas dan hasil belajar siswa.